Defense Logistics Management in Border Areas - Hermanto, Djamarel; Saragih, Herlina Juni Risma (The Republic of Indonesia Defense University, 2025)
This article thoroughly investigates the optimization of defense logistics management within national border areas, with a distinct focus on integrating a